Psychological and physiological benefits of horticultural therapy for Chinese older adults - Li Xiaoyi; Ahmad Hassan; Jiang Tao; Zhang Deshun (SAGE Publishing, 2024)
Background Gardening as a leisure activity has been shown to be potentially beneficial for older adults, this study aimed to assess the physiological and psychological impacts of a specific horticultural activity, watering indoor plants, compared with playing a computer game - the Klondike Solitaire Card Game. Methods This crossover study included 100 older adults recruited from a nursing care facility for older people in Shanghai, China. They were allocated to either engage in watering indoor plants (horticultural group) or playing a computer game (control group). For the inclusion criteria, screening for cognitive function was conducted to exclude those with severe cognitive impairments, thereby focusing on those capable of participating fully in the study activities. Brainwave activities, blood pressure, and psychological states were measured through pre- and post-test questionnaires to evaluate the physiological and psychological effects. Results The activity of watering indoor plants was associated with significant reductions in both systolic and diastolic blood pressure, in contrast to the computer game activity. Additionally, participants in the horticultural group showed increased brainwave mean values, indicating heightened relaxation and focus, while decreases were observed in the control group. The experimental group reported reduced anxiety scores, along with increased feelings of comfort and relaxation, and also exhibited significantly higher meditation levels, which indicates a profound mental relaxation effect. Conclusion Our findings suggest that engaging in indoor horticultural activities, such as watering houseplants for 10 minutes, can reduce mental and physical stress levels in older adults.